Optimisation of cinnamaldehyde-in-water nanoemulsion formulation using central composite rotatable design - Asmawati M. Sail,; Wan Aida Wan Mustapha,; Salma Mohamad Yusop,; Mohamad Yusof Maskat,; Ahmad Fuad Shamsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Thirteen formulations of cinnamaldehyde/non-ionic surfactant/water system nanoemulsions were prepared using high-pressure homogenisation. The result showed that varying the cinnamaldehyde/surfactant ratio had effect significantly (p<0.05) to mean droplet diameter, polidispersity index, ζ-potential, turbidity and whiteness index, while no significant effect (p>0.05) to viscosity. The mean droplet diameter ranged from 50.48 to 106.4 nm, polydispersity index from 0.06 to 0.28 and ζ-potential from -4.11 to -6.98 mV. The smallest droplet size was produced using 5% cinnamaldehyde and 5% Tween 80. Response surface for droplet diameter showed that the higher the cinnamaldehyde and surfactant concentrations, the larger the droplet diameter, polydispersity index and whiteness index. However, the ζ-potential increased as the cinnamaldehyde concentration decreased and Tween 80 increased. Increasing the cinnamaldehyde concentration led to an increase in turbidity. Formulation of 5% cinnamaldehyde and 6.23% Tween 80 gave no observable separation of the nanoemulsion with minimum droplet size, polidispersity index, viscosity, turbidity, whiteness index and maximum ζ-potential in modulus. The stability of the optimum formulation was sustained for 10 days upon storage at 4°C. The values of droplet diameter, PDI and ζ-potential were 55.50 nm, 0.08 and -5.38 mV, respectively.